Habituasi One Teacher One Language Dalam Pembelajaran Multibahasa Pada Taman Kanak-Kanak - Andari, Ida Ayu Made Yuni; Antara, Putu Aditya; Asril, Nice Maylani (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2024)
The research aims to examine the habituation of multilingual learning with the “One Teacher One Language” method in the kindergarten of Sekolah Nasional 3 Bahasa Budi Luhur. This type of research is qualitative research with a case study approach, data collection methods are classroom observation, interviews and documentation. The subject of this research is a kindergarten at the national Sekolah Nasional 3 Bahasa Budi Luhur. This research procedure is the description or orientation stage, the reduction stage and the selection stage. The instruments of this research are research grids, observation guidelines, interview guidelines, field notes, and checklists. The data analysis of this research is data reduction, data model, conclusion drawing/verification. The results of the analysis show that the theories of interlanguage, constructivism, and second language learning provide a strong foundation for the One Teacher One Language strategy. Constraints in implementation, such as time sharing and variations in teacher skills, require attention to theoretical principles, such as the Zone of Proximal Development (ZPD) and the use of scaffolding. However, the integration of language in the learning process, diverse learning strategies, direct interaction between teachers and students, and cultural activities demonstrate a comprehensive effort in creating a dynamic and inclusive learning environment.